The panchromatic Hubble Andromeda treasury. V. ages and masses of the year 1 stellar clusters - Fouesneau, Morgan; Johnson, L. Clifton; Weisz, Daniel R.; Dalcanton, Julianne J.; Bell, Eric F.; Bianchi, Luciana; Caldwell, Nelson; Gouliermis, Dimitrios A.; Guhathakurta, Puragra; Kalirai, Jason; Larsen, Søren S.; Rix, Hans-Walter; et al. (The astrophysical journal, 2014)
We present ages and masses for 601 star clusters in M31 from the analysis of the six filter integrated light measurements from near-ultraviolet to near-infrared wavelengths, made as part of the Panchromatic Hubble Andromeda Treasury (PHAT). We derive the ages and masses using a probabilistic technique, which accounts for the effects of stochastic sampling of the stellar initial mass function. Tests on synthetic data show that this method, in conjunction with the exquisite sensitivity of the PHAT observations and their broad wavelength baseline, provides robust age and mass recovery for clusters ranging from ∼102 to 2 × 106 M ☉. We find that the cluster age distribution is consistent with being uniform over the past 100 Myr, which suggests a weak effect of cluster disruption within M31. The age distribution of older (>100 Myr) clusters falls toward old ages, consistent with a power-law decline of index -1, likely from a combination of fading and disruption of the clusters. We find that the mass distribution of the whole sample can be well described by a single power law with a spectral index of -1.9 ± 0.1 over the range of 103-3 × 105 M ☉. However, if we subdivide the sample by galactocentric radius, we find that the age distributions remain unchanged. However, the mass spectral index varies significantly, showing best-fit values between -2.2 and -1.8, with the shallower slope in the highest star formation intensity regions. We explore the robustness of our study to potential systematics and conclude that the cluster mass function may vary with respect to environment.